Myocysticercosis of hand - A case report on a rare presentation - Puri, Kshiteez; Mishra, Bibhuti Nath (Grande Medical Journal, 2024)
Isolated Thenar muscle involvement of Taenia solium larva causing myocysticercosis is rarely reported in literature. A high degree of suspicion has to be kept in the people of endemic regions in developing county with an ethical background of pork consumption in regular diet. Ultrasound is the first investigation to look for, however, MRI can further aid to the diagnosis. Different treatment options including observation, surgical excision, anti-helminthic and anti-inflammatory medication.